Cardiac surgery in patients with Hemophilia:is it safe? - Shalabi, Amjad (J Cardiothorac Surg, 2020)
BACKGROUND: The life expectancy of hemophiliacs is similar to that of the general population. As a result, the prevalence of age-related cardiovascular diseases has increased. We present our experience with hemophilia patients who underwent cardiac surgery in our Medical Center between 2004 and 2019. METHODS: All hemophilia patients who underwent cardiac surgery were identified, and their peri-operative data evaluated retrospectively. RESULTS: Ten patients were identified: six with hemophilia-A, one with hemophilia-B, and three with hemophilia-C (factor XI deficiency). Cardiac procedures included ten coronary artery bypass grafts and one aortic valve replacement. Hemophilia-A and B patients were treated with factor substitution, whereas patients with factor XI deficiency were treated with fresh frozen plasma. One patient died, and one patient suffered from non-active gastrointestinal bleeding. CONCLUSIONS: While major cardiac surgery can be performed safely on patients with hemophilia, a multidisciplinary team approach and strict postoperative monitoring are essential in order to achieve optimal results.